(untitled) (World Bulletin of Social Sciences, 2025)
This article discusses the composition, themes, and hermeneutics of the works of Arshiy Termiziy, a member of the Termiziy Sayyid family. It also analyzes how the philosopher depicted the ethics of the perfect human being in a unique manner. The role of didactic poetic genres in the education of a well-rounded personality is also highlighted.